PSYCHOLOGICAL AND PEDAGOGICAL FEATURES OF PROFESSIONAL COMPETENCE MODELING IN PROFESSIONAL DEVELOPMENT OF MEDICAL STUDENTS - Lazurenko, Olena (PSYCHOLOGICAL JOURNAL, 2018)
The article is devoted to the problem of professional development of a specialist. One of the tasks of the system of national higher education is the training of highly skilled specialists. The analysis of scientific sources suggests that the problem of studying professional development is in the constant focus of many scholars who determine the nature and stages of professional development, psychological peculiarities, psychological and pedagogical conditions and factors of professional development of the individual. The problem of studying the peculiarities of the professional competence of doctors in the process of professional development and its influence on professional activity remains insufficiently investigated, and the insufficient level of development of professional competence of graduates of medical universities negatively affects the effectiveness of future professional activities. The formation of professionalism of a future specialist depends on educational and cognitive activity, which encompasses not only mastering of the system of knowledge, acquisition of skills and abilities, but also constant self-improvement. The essence and stages of professional formation are determined. Professional formation of a personality is a holistic dynamic process from the formation of professional self-determination to the full realization of oneself in the activity. Professional formation of the person has two vectors - educational and personal growth. Professionalism is an indispensable component of competence in a particular activity. The stages of development of the doctor in the professional sphere, stages of formation of professional abilities in the process of mastering the profession are considered. The general characteristic of professional formation and level of professionalism is given. Competence is defined as the acquired experience as a long process of acquiring the skills and skills necessary to achieve a high level of mastery in a particular area of ​​life, in particular professional. Given the specifics of the professional activities of the doctor, an important factor in its effectiveness is professional competence. The main task of training and education, the result of professional development of a specialist in a higher medical school is the formation of professional competence of medical students. The professional competence of a doctor is a complex of skills acquired in the process of training the knowledge, skills and abilities necessary for the performance of their professional duties. The model of professional formation and formation of professional competence of the future doctor is presented. The analysis of stages of professional formation of specialists is presented, psychological and pedagogical peculiarities of formation of professional competence of future physicians at the stage of professional formation are determined. The stages of professional psychology of the personality of the doctor from the stage of professional psychological readiness and adaptation to the stage of professional skill are outlined. Analyzed psychological and pedagogical peculiarities of the professional formation of the future physician allow us to talk about the possibility of developing professional competence of a specialist. Educational process of preparation of the future doctor should provide not only professional, but also personal development of a specialist, both at the stage of pre-diploma, and at the stage of postgraduate training. The analysis of the concepts and models of professional and personal development and the formation of specialists at the stage of professional training was carried out in our previous studies. It allowed identifying and outlining several phases of the person's professional psychology from the stage of professional psychological readiness and adaptation to the stage of professional mastery, the source of which is not only the personal qualities of the doctor, but also his professional competencies. A detailed analysis of the psychological peculiarities of the professional development of a future physician allowed us to talk about the possibility of developing professional competence of a specialist. Based on this analysis, it can be assumed that the acquisition of knowledge, skills and abilities associated with the professional competence of a doctor will promote the development of professionalism as an integral quality of the personality of a specialist. The concept of professional development of the physician's personality allows us to conclude that the professionalism of the personality of the doctor and his professionalism are realized in professional activity. Each stage of professional development is characterized by a peculiar combination of personality and professional features, which are manifested in the process of professional activity, which, in turn, requires the former professional competence of the doctor. The results of the research on the problem of professional development of the individual, the formation of professional competence of a specialist in a higher medical school dictate the urgent need for continuation and further study of the features of the doctor’s professional training.